Enrollment and Distribution of Disabled at Primary Schools in Nepal - Rijal, Shiba Prasad (The Third Pole: Journal of Geography Education, 2014)
The issue of education for disabled children is of major concern with a view to achieve the goal of universal primary education. Nepal, being a signatory of Education for All and the Salamanca Declaration (1994), has adopted a policy of inclusive education ensuring the presence, participation and achievement of children having different abilities in the schools. Altogether 53,681children (1.3percent of the total enrolment) having different abilities were enrolled at primary schools of Nepal in 2009. Of them the proportion of children with physical and mental disabilities was high as compared to other types. The enrolment of disabled children varies spatially by region and district. Among disabled enrolled at primary school, The Western and Mid-western Mountain Region share the highest proportion i.e. 3.7 percent each. Among district, Surkhet shows the highest proportion (4.3 percent) of disabled children enrolled. Socio-economic condition of the household and disability of children are directly or indirectly interlinked. The positive correlation between district level Human Poverty Index (HPI) and enrolment of children having disability clearly show this. However, the role of other factors cannot be undermined. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11553 The Third Pole Vol. 11-12 Page : 45-49